Spectrum of histopathological patterns of breast lesions in a tertiary care hospital - Akinapally Mrudula; Mohd Imran Ali; Swathi Samalla; Rajarikam Nagarjuna Chary (Asian Journal of Medical Sciences, 2023)
Background: Breast lesions are areas of abnormal breast tissue. It is estimated that 20% of women develop breast lesions. Breast lesions are either benign or malignant. Breast carcinomas are the most common cause of deaths in women accounting for 10.6% deaths in India, 6.9% deaths per year globally. Aims and Objectives: To study various histopathological patterns of breast lesions in women admitted in Government General Hospital. Materials and Methods: It is a prospective study in the department of pathology, Government General Hospital, Nizamabad, from December 2020 to July 2022. Grossing was done and details noted, tissue bits were processed and sections were stained with conventional H and E Staining. Results: Out of 70 cases of breast lesions, 55 (78.5%) are benign breast lesions and 15 (21.5%) are malignant breast lesions. Fibroadenoma is the most common breast lesion accounting for 33 cases, that is, 60 %, followed by fibrocystic diseases (21.8%). Infiltrating ductal carcinoma of No Special Type is the most common malignant breast lesion accounting for 10 cases, that is, 66.6%. Among invasive breast carcinomas, the majority of cases are Grade II (69%). Conclusion: Study of histopathological patterns of breast lesions plays an important role in diagnosis, treatment, and prognosis of breast lesions. This study highlighted incidence and pathological characteristics of a wide range of breast lesions.